2014
DOI: 10.1039/c4dt00711e
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite films as building blocks for antireflective coatings and vapor responsive Bragg stacks

Abstract: Zeolite films (LTL, BEA and MFI) are prepared with a thickness in the range 50-170 nm through a multistep spin-on deposition method. The optical properties of the zeolite films including refractive index, extinction coefficient and thickness are determined from the reflectance spectra using a nonlinear curve fitting method. The total free pore volume of the films using the Bruggeman effective medium theory is calculated. The potential of the zeolite films for broadband antireflection (AR) application is demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…It is seen from Figure 4 that the refractive index of the TEOS-LTL composites annealed at both temperatures was substantially lower compared to the TEOS-only layers. The reason is that the refractive index of the LTL zeolites (~1.37) [16] is less than the refractive index of the TEOS matrix, and thus LTL addition reduces the effective refractive index of the composite. Furthermore, the annealing at higher temperature also led to a reduction in the refractive index; this effect was most pronounced for doped samples.…”
Section: Studies Of Film N and D Due To Exposure To Watermentioning
confidence: 99%
“…It is seen from Figure 4 that the refractive index of the TEOS-LTL composites annealed at both temperatures was substantially lower compared to the TEOS-only layers. The reason is that the refractive index of the LTL zeolites (~1.37) [16] is less than the refractive index of the TEOS matrix, and thus LTL addition reduces the effective refractive index of the composite. Furthermore, the annealing at higher temperature also led to a reduction in the refractive index; this effect was most pronounced for doped samples.…”
Section: Studies Of Film N and D Due To Exposure To Watermentioning
confidence: 99%
“…Mesoporous materials (pore diameter in the range of 2-50 nm) have attracted the scientific interest due to their remarkable properties and potential applications in many advanced areas such as drug delivery systems, sensors, catalysis, photovoltaic cells, and fuel cells [9]. One attractive application of the mesoporous films can be realized when they are incorporated in one-dimensional stacks (Bragg stacks) as high refractive index building blocks [10,11]. In this case, an optical sensing could be realized on the basis of refractive index change due to the condensation of vapors in the pores [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Nb 2 O 5 is a high refractive index material and could be assembled in thin film form by simple methods [14]. Besides, recently we have reported that Nb 2 O 5 could be successfully used as a high refractive index building block of a vapor responsive Bragg stack that comprises MFI zeolite as sensing element [15]. Zeolites are crystalline materials with framework-type structures built of regular and uniform pores of molecular dimensions [16].…”
Section: Introductionmentioning
confidence: 99%